Guided reconstitution of membrane protein fragments. Issue 1 (January 2014) - Cohen, Leah S.; Arshava, Boris; Kauffman, Sarah; Mathew, Elizabeth; Fracchiolla, Katrina E.; Ding, Fa‐Xiang; Dumont, Mark E.; Becker, Jeffrey M.; Naider, Fred
ABSTRACT Structural analysis by NMR of G protein‐coupled receptors (GPCRs) has proven to be extremely challenging. To reduce the number of peaks in the NMR spectra by segmentally labeling a GPCR, we have developed a Guided Reconstitution method that includes the use of charged residues and Cys activation to drive heterodimeric disulfide bond formation. Three different cysteine‐activating reagents: 5‐5′‐dithiobis(2‐nitrobenzoic acid) [DTNB], 2, 2′‐dithiobis(5‐nitropyridine) [DTNP], and 4, 4′‐dipyridyl disulfide [4‐PDS] were analyzed to determine their efficiency in heterodimer formation at different pHs. Short peptides representing the N‐terminal (NT) and C‐terminal (CT) regions of the first extracellular loop (EL1) of Ste2p, the Saccharomyces cerevisiae alpha‐factor mating receptor, were activated using these reagents and the efficiencies of activation and rates of heterodimerization were analyzed. Activation of NT peptides with DTNP and 4‐PDS resulted in about 60% yield, but heterodimerization was rapid and nearly quantitative. Double transmembrane domain protein fragments were biosynthesized and used in Guided Reconstitution reactions. A 102‐residue fragment, 2TM‐tail [Ste2p(G31‐I120C)], was heterodimerized with CT‐EL1‐tailDTNP at pH 4.6 with a yield of ∼75%. A 132‐residue fragment, 2TMlong‐tail [Ste2p(M1‐I120C)], was expressed in both unlabeled and 15N‐labeled forms and used with a peptide comprising the third transmembrane domain, to generate a 180‐residue segmentally labeled 3TM protein that was found to be segmentally labeled using [15N, 1H]‐HSQC analysis. Our data indicate that the Guided Reconstitution method would be applicable to the segmental labeling of a membrane protein with 3 transmembrane domains and may prove useful in the preparation of an intact reconstituted GPCR for use in biophysical analysis and structure determination. © 2013 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 102: 16–29, 2014.